Advances in the Diagnosis and Management of Pulpitis: A Comprehensive Clinical and Research Based Approach - Elnazarov Azamat Toʻlqin oʻgʻli (American Journal of Bioscience and Clinical Integrity, 2025)
Pulpitis, a prevalent dental condition characterized by inflammation of the dental pulp, poses a significant challenge in dental practice due to its complex pathology and variable clinical presentations. The advent of modern diagnostic tools and the refinement of treatment techniques have revolutionized the management of both reversible and irreversible forms of pulpitis. This article provides a comprehensive overview of the pathophysiology, diagnostic advancements, and clinical strategies employed in managing pulpitis. It emphasizes the role of vital pulp therapy, pulp sensibility tests, biomaterials such as MTA and biodentine, and minimally invasive procedures aimed at preserving tooth vitality. The study also discusses the integration of imaging technologies such as CBCT and thermal imaging into diagnostic protocols, presenting results from a clinical study involving 150 patients. Comparative analyses and outcomes highlight evidence-based improvements in treatment success. The findings advocate for a paradigm shift from traditional to biologically driven endodontic therapy, reinforcing patient-centered approaches.